Socio-economic patterning of food consumption and dietary diversity among Indian children: evidence from NFHS-4 - Agrawal, Sutapa; Kim, Rockli; Gausman, Jewel; Sharma, Smriti; Sankar, Rajan; Joe, William; Subramanian, S. V. (European journal of clinical nutrition, 2019)
Background/Objectives Most interventions to foster child growth and development in India focus on improving food quality and quantity. We aimed to assess the pattern in food consumption and dietary diversity by socioeconomic status (SES) among Indian children. Subjects/Methods The most recent nationally representative, cross-sectional data from the National Family Health Survey (NFHS-4, 2015–16) was used for analysis of 73,852–74,038 children aged 6–23 months. Consumption of 21 food items, seven food groups, and adequately diversified dietary intake (ADDI) was collected through mother’s 24-h dietary recall. Logistic regression models were conducted to assess the association between household wealth and maternal education with food consumption and ADDI, after controlling for covariates. Results Overall, the mean dietary diversity score was low (2.26; 95% CI:2.24–2.27) and the prevalence of ADDI was only 23%. Both household wealth and maternal education were significantly associated with ADDI (OR:1.28; 95% CI:1.18–1.38 and OR:1.75; 95% CI:1.63–1.90, respectively), but the SES gradient was not particularly strong. Furthermore, the associations between SES and consumption of individual food items and food groups were not consistent. Maternal education was more strongly associated with consumption of essential food items and all food groups, but household wealth was found to have significant influence on intake of dairy group only. Conclusions Interventions designed to improve food consumption and diversified dietary intake among Indian children need to be universal in their targeting given the overall high prevalence of inadequate dietary diversity and the relatively small differentials by SES.